Kepadatan Stok, Komposisi Jenis, Struktur Ukuran dan Daerah Penangkapan Ikan di Teluk Jakarta - Wagiyo, Prihatiningsih; p, Prihatiningsih; Turni Hartati, Sri (Jurnal Riset Jakarta, 2021)
Jakarta Bay has a variety of biota as a fishery resource, the utilization of which is continuous intensively. this study aims to obtain the data and information on stock density, species composition, size structure and fishing ground. The research was conducted by means of exploration and observation in 2016. The results showed that the average stock density in Jakarta Bay was 11,400 kg/km2 and in the Seribu Islands 25,500 kg/km2. Stock density distribution based on vertical coastline is obtained; mouth part 13,925 kg/km2, middle 11,709 kg/km2 and the coast 8,326 kg/km2. Coastal horizontal distribution; West area 15,311 kg/km2, Central 9,256 kg/km2 and East 9,259 kg/km2. Based on area in the Seribu Islands 25,500 kg/km2, Jakarta Bay 11,320 kg/km2 and Tangerang 11,610 kg/km2. Stock composition includes; demersal fish 84.53%, Cephalopods 9.98%, Crustaceae 4.32% and others. The fishing area of gill nets is wider and more spread out than other fishing gear.